2005
DOI: 10.1177/194589240501900517
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Anterior Skull Base Tumors: Comparison of Combined Traditional and Endoscopic Techniques

Abstract: In this preliminary study, MIER of ASB neoplasia did not differ significantly from tCFR in operative time, estimated blood loss, hospital stay, or complication rate. Survival and recurrence rates were similar also. This early experience suggests that MIER is a viable alternative for the surgical management of ASB lesions in appropriately selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
149
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(166 citation statements)
references
References 22 publications
11
149
0
6
Order By: Relevance
“…Ever since the advent of nasal endoscopic surgeries [13] and its exploration in the field of oncological surgeries, much has been debated and currently consensus is to use it in early staged diseases and in advanced stage for debulking [14]. Issues of piecemeal resection-tumour spillage and adequacy of margin, during endoscopic surgeries have been discussed by Bogaerts et al [15] and endoscopic resection has been concluded to be safe in terms of disease clearance and overall survival with reduced morbidity, in selected cases like carcinomas of ethmoids without intradural extension, similar results have been replicated by Arnold et al [16].…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the advent of nasal endoscopic surgeries [13] and its exploration in the field of oncological surgeries, much has been debated and currently consensus is to use it in early staged diseases and in advanced stage for debulking [14]. Issues of piecemeal resection-tumour spillage and adequacy of margin, during endoscopic surgeries have been discussed by Bogaerts et al [15] and endoscopic resection has been concluded to be safe in terms of disease clearance and overall survival with reduced morbidity, in selected cases like carcinomas of ethmoids without intradural extension, similar results have been replicated by Arnold et al [16].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies with small samples have suggested that endoscopic resections are at least as efficacious as open approaches with decreased morbidity as well the theoretical advantages of a possible decrease in intensive care unit and overall hospital stay [7,9] .…”
mentioning
confidence: 99%
“…Initial authors described skull base surgery in the context of continued bifrontal craniotomy, sparing the cosmetic effects of a facial incision [4][5][6] . More recent authors have described entirely endoscopic techniques, sparing both facial incisions and the morbidity of craniotomy [7][8][9][10][11][12] . Avoidance of piecemeal techniques is a theoretical advantage of CFR over endoscopic techniques.…”
mentioning
confidence: 99%
“…Many other neoplasms involving the anterior skull base have been approached through the endonasal route such as esthesioneuroblastomas (Suriano et al, 2007), nasopharyngeal fibromas and carcinomas (Batra et al, 2005).…”
Section: Anterior Skull Base Neoplasmsmentioning
confidence: 99%